TRANSGENE COPY NUMBER AND PHENOTYPIC VARIATIONS IN TRANSGENIC BASMATI RICE - Mahmood-ur-Rahman; A. Q. Rao; F. Batool; S. Azam; A. A. Shahid; T. Husnain (Journal of Animal and Plant Sciences, 2012)
Bt genes were detected on metaphase chromosomes of transgenic Basmati rice in order to find out the effects of copy number and location of transgene (s) on important agronomic traits of transgenic Bt rice. Phenotypic traits of transgenic plants highly varied from control. The transgenic plants were shorter in height and internodal length and were early maturing. Awns were totally absent in transgenic plants containing two Bt genes. Integration of the Bt genes on the host genome and their copy number was determined through Fluorescence in situ hybridization. No correlation was found between presence of Bt genes on different chromosomes and phenotypic traits. However, transgene copy number was found negatively correlated with agronomic traits. With the increase in copy number of transgene (s), the plant height, internodal length and days to maturity were decreased. Positive correlation was found between the Bt protein concentration and transgene copy number. The concentration of Bt protein was higher in plants having more copies of transgene indicating that copy number and not the location of the transgene determined phenotypic variation in transgenic plants.
Keywords: Bt rice; FISH; Position Effect; Copy Number; Transgene